The impact of type 1a endoleak on the long-term outcome after EVAR. Issue 5 (3rd September 2021) - Van Slambrouck, Jan; Mufty, Hozan; Maleux, Geert; Houthoofd, Sabrina; Devooght, Anne; Slots, Charlotte; Daenens, Kim; Fourneau, Inge
Abstract: Objective: Endoleaks remains a major determinant of outcome after endovascular aortic repair (EVAR) for infrarenal abdominal aortic aneurysms. The objective of this study is to evaluate the long-term impact of proximal type 1 endoleak encountered at the case end of the EVAR procedure or during follow-up. Methods: All patients treated with EVAR between February 2001 and August 2017 in our institution were included. Data were collected retrospectively. A descriptive analysis of subgroups with type 1a endoleak at case end or with type 1a endoleak first encountered during follow-up was performed. Results: In total, 468 patients were included for analysis. At the case end of the EVAR procedure, in 5.3% (25/468) of patients, a type 1a endoleak was seen. In 72% of cases (18/25) the type 1a endoleak spontaneously disappeared on the first follow-up computed tomography angiography and never recurred. At the end of the follow-up period, no patient in this subgroup died with a type 1a endoleak on follow-up. In 3.4% (16/468) of all cases, a type 1a endoleak was encountered for the first time during follow-up. In 87.5% (14/16) of these cases, reintervention was performed. Two patients died with a persisting type 1a endoleak during follow-up. Conclusions: Clinicians should differentiate between the type 1a endoleak at the case end and the type 1a endoleak first occurring during follow-up. For type 1a endoleak at the case end, expectant management can be adopted. Delayed type 1a endoleak seen during follow-up rarely seals spontaneously and needs reintervention in the majority of cases.